Risk factors for rectal stump leakage after discontinuity resection: stump length matters most - Ritter, Alina; Dumm, Noemi; Deisenhofer, Julian; Franz, Clemens; Saeedi, Mohammed al; Büchler, Markus W.; Schneider, Martin (Diseases of the colon & rectum, 2024)
BACKGROUND: - Discontinuity resection is commonly conducted to avoid anastomotic leakage in high-risk patients but potentially results in rectal stump leakage. Although risk factors for anastomotic leakage have been widely studied, data on rectal stump leakage rates and underlying risk factors are scarce. - OBJECTIVE: - To determine rectal stump leakage rates following Hartmann’s procedure and to identify patient-and surgery-associated risk factors. - DESIGN: - A retrospective study with univariate and multivariate analyses was performed to identify risk factors of rectal stump leakage. A subgroup analysis of scheduled operations was performed. - SETTINGS: - The study was conducted at Heidelberg University Hospital, Germany. - PATIENTS: - Patients were included who underwent discontinuity resection with rectal stump formation between 2010 and 2020. - MAIN OUTCOME MEASURES: - The main outcome measures included rectal stump leakage rates, 30-day mortality, length of hospitalization, and necessity for further invasive treatment. - RESULTS: - Rectal stump leakage occurred in 11.78% of patients. Rectal stump leakage rates varied considerably depending on the surgical procedure performed and were highest following subtotal pelvic exenteration (34%). Diagnosis of rectal stump leakage peaked on postoperative day 7. A short rectal stump (p = 0.001), previous pelvic radiotherapy (p = 0.04), chemotherapy (p = 0.004), and previous laparotomy (p = 0.03) were independent risk factors for rectal stump leakage in the entire patient collective. In patients undergoing scheduled surgery, a short rectal stump was the only independent risk factor (p = 0.003). Rectal stump leakage was not associated with increased 30-day mortality but prolonged length of hospitalization and frequently necessitated further invasive treatment. - LIMITATIONS: - Study results are limited by the retrospective design, a high number of emergency operations, and the mere inclusion of symptomatic leakages. - CONCLUSIONS: - Rectal stump leakage is a relevant complication after discontinuity resection. Risk factors should be considered during surgical decision-making when both discontinuity resection and abdominoperineal resection are feasible.